Envisioning how fair use and fair dealing might best facilitate scholarship. Issue 1 (2015) - Caidi, Nadia; Centivany, Alissa; Samuelson, Pam; Wolfe, Michael
ABSTRACT: Copyright law grants exclusive rights to authors of original works of authorship, but those rights are subject to numerous exceptions and limitations, including fair use in the United States and fair dealing in Canada. These exceptions have traditionally worked to ensure that the rights of copyright owners are adequately balanced with the interests of subsequent authors, researchers, and consumers of copyrighted works. Moreover, fair use has emerged as the most promising legal mechanism for the digitization, preservation, and study of large collections of copyrighted work. Fair use and fair dealing provide much of the flexibility needed to ensure that copyright protection serves to facilitate scholarship rather than threaten it. Scholars encounter copyright law both as authors and as users of copyrighted works. With an eye toward the future, this panel will examine the extent to which the discourses and practices of the past decade have contributed to shaping and reshaping our scholarly environment, how the information field has responded, and why and how information scholars, researchers and professionals ought to remain engaged in these matters in the future.